The impact of low cost airlines to airline industry: An experience of Thailand - Komsan Suriya (2018)
The deregulation of airline industry of Thailand has allowed three low cost airlines (LCAs) to operate in domestic routes. This study explored the impact of LCAs to three stakeholders in airline industry, full-service airlines, airports and passengers. The main question was who gained or lost from LCAs. In answering the question, the demand for airline industry was estimated. The change in revenue of airlines and airports were considered as private benefits. The change in consumer's surplus, amount of money that passengers were willing to pay for the airfare but did not pay, was regarded as the social benefit. Comparison of benefits between the expansion and recession periods of the airline industry were examined. Moreover, the change in traveling pattern from Thailand to Laos was also investigated. This study proved that, in the expansion period, LCAs were not harmful to full-service airlines. In turn, they were important to the growth of the industry. However in the recession period, LCAs were growing at the expense of full-service airlines. For passengers, consumer's surplus was increased in the expansion period but decreased in the recession period due to higher airfare. A irports gained in both expansion and recession period. LCAs encouraged tourists to change their traveling pattern from Thailand to Laos via an indirect route, Bangkok - Udorn Thani - Nongkai - the Friendship Bridge instead of the direct route from Bangkok to Vientiane.